Influence of Firm Size, Profitability and Size of Board of Commissioners on Corporate Social Responsibility Disclosure - Uzliawati, Lia; Rosiana, Rita; Samudi, Muhamad Samudi (Universitas Serang Raya, 2015)
This study aims to analyze influence of Firm Size , Profitability and Size of Board of Commissioners Against Corporate Social Responsibility Disclosure . The independent variable in this study consists of company size, profitability and board size. Profitability variables in this study by Return on Assets (ROA). While disclosure of Corporate Social Responsibility Disclosure using 22 items taken from the GRI (2006), which is the research and Afni Suhardjanto (2009 ) . The sample used is a banking company that is listed on the Indonesia Stock Exchange during the period 2010 - 2012 with a total of 93 samples used were firm observation years. The analysis model used in this study is a multiple linear regression using SPSS software version 20.0. Based on the results of multiple linear regression, the study found that firm size, profitability, and the board size to the CSR significant negative effect. Keyword: Firm Size, Profitability, Board size, Corporate Social Responsibility Disclosure and Stakeholder